Renoprotective Effect of Dipeptidyl Peptidase-4 Inhibitors in Patients with Type 2 Diabetes Mellitus - Esaki, Hiroki; Tachi, Tomoya; Goto, Chitoshi; Sugita, Ikuto; Kanematsu, Yuta; Yoshida, Aki; Saito, Kosuke; Noguchi, Yoshihiro; Ohno, Yuki; Aoyama, Satoshi; Yasuda, Masahiro; Mizui, Takashi; et al. (Frontiers in Pharmacology, 2017)
Diabetic nephropathy is one of three major complications of diabetes mellitus, often leading to chronic renal failure requiring dialysis. By enhancing glucagon-like peptide 1 activity, recently developed dipeptidyl peptidase-4 (DPP-4) inhibitors may possess renoprotective effects in addition to antihyperglycemic effects. In this study, we retrospectively investigated temporal changes in renal function index of type 2 diabetes patients and examined the influence of DPP-4 inhibitors on renal function. Diabetes mellitus type 2 patients (>18 years old) prescribed hypoglycemic agents at Gifu Municipal Hospital for ≥3 months between March 2010 and April 2014 were included in the study. Renal function was evaluated as estimated 12-month glomerular filtration rate decline from baseline in patients receiving and not receiving DPP-4 inhibitors. Patient data from DPP-4 inhibitors group (501 patients, 58.6%) and DPP-4 inhibitors-untreated group (354, 41.4%), were analyzed using multiple logistic regression analysis, as well as Cox proportional-hazards regression analysis (616, 55.6% and 491, 44.4%, for DPP-4 inhibitors-treated and untreated group). Multiple logistic regression analysis indicated that DPP-4 inhibitors significantly lowered estimated glomerular filtration rate decline (20% over 12 months; odds ratio, 0.626; 95% CI, 0.409-0.958; P = 0.031). Similar results were obtained using Cox proportional-hazards regression analysis (hazard ratio, 0.707; 95% CI, 0.572-0.874; P = 0.001). These findings suggest that DPP-4 inhibitors suppress the decrease of estimated glomerular filtration rate in type 2 diabetes mellitus patients and show a renoprotective effect.